Directed growth of graphene nanomesh in purified argon via chemical vapor deposition. (25th May 2017) - Sun, Haibin; Fu, Can; Shen, Xia; Yang, Wenchao; Guo, Pengfei; Lu, Yang; Luo, Yongsong; Yu, Benhai; Wang, Xiaoge; Wang, Chunlei; Xu, Junqi; Liu, Jiangfeng; et al.
Abstract: Graphene nanomeshes (GNMs), new graphene nanostructures with tunable bandgaps, are potential building blocks for future electronic or photonic devices, and energy storage and conversion materials. In previous works, GNMs have been successfully prepared on Cu foils by the H2 etching effect. In this paper, we investigated the effect of Ar on the preparation of GNMs, and how the mean density and shape of them vary with growth time. In addition, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (TEM) revealed the typical hexagonal structure of GNM. Atomic force microscopy (AFM) and x-ray photoelectron spectroscopy (XPS) indicated that large copper oxide nanoparticles produced by oxidization in purified Ar can play an essential catalytic role in preparing GNMs. Then, we exhibited the key reaction details for each growth process and proposed a growth mechanism of GNMs in purified Ar.